2006
DOI: 10.1093/carcin/bgl004
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of histone modifications and transgene silencing by nickel chloride

Abstract: Although it has been well established that insoluble nickel compounds are potent carcinogens and soluble nickel compounds are less potent, the mechanisms remain unclear. Nickel compounds are weakly mutagenic, but cause epigenetic effects in cells. Previous studies have shown that insoluble nickel compounds enter cells by phagocytosis and silence gene expression, but the entry of soluble nickel compounds and their effects on gene silencing have not been well studied. Here, we have demonstrated, using a dye that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(93 citation statements)
references
References 46 publications
4
87
1
1
Order By: Relevance
“…Previous studies have shown that nickel exposure results in alteration of histone modifications in cells, and thereby disrupts epigenetic homeostasis. A loss of histone acetylation and an increased histone methylation on H3K9 were previously observed in nickel-exposed cells Ke et al, 2006;Ke, 2007). In this study, it has been demonstrated that nickel compounds, both soluble NiCl 2 and insoluble Ni 3 S 2 , increase histone ubiquitination of H2A and H2B in A549 cells in a dose-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Previous studies have shown that nickel exposure results in alteration of histone modifications in cells, and thereby disrupts epigenetic homeostasis. A loss of histone acetylation and an increased histone methylation on H3K9 were previously observed in nickel-exposed cells Ke et al, 2006;Ke, 2007). In this study, it has been demonstrated that nickel compounds, both soluble NiCl 2 and insoluble Ni 3 S 2 , increase histone ubiquitination of H2A and H2B in A549 cells in a dose-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 58%
“…This nickel-induced transgene silencing did not involve mutation or deletion of any portion of the transgene (Lee et al, 1995). Instead, increased DNA methylation and chromatin condensation (Lee et al, 1995), as well as a broad loss of histone acetylation of all four core histones and an increase in histone H3K9 methylation were observed at the silenced transgene locus (Yan et al, 2003;Ke et al, 2006). This indicated that an epigenetic, rather than a mutagenic mechanism was involved in the nickel-induced transgene silencing.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Ni-induced spreading of H3K9me2 is reminiscent of the local discrete changes, suggesting that misregulation of this regulatory switch results in altered gene expression. Furthermore, several earlier studies have suggested ectopic spreading of H3K9me2 to be an important signal for transcriptional silencing (27)(28)(29)(30)39). However, the alternate possibility of gene silencing resulting in spreading of H3K9me2 in a subset of the spreading domains cannot be ruled out.…”
Section: Discussionmentioning
confidence: 95%
“…that showed association of H3K9me2 spreading with decreased gene expression (27)(28)(29)(30). To examine this on a genome-wide scale, we stratified all of the genes into those in H3K9me2-spreading domains (3,930) and genes that are not in H3K9me2 in either control or Ni-exposed cells (8,096) ( Fig.…”
Section: Resultsmentioning
confidence: 99%